Alignments of instruments and action in governance: a synthesis – revisited and extended. Issue 1 (2nd January 2016) - Thynne, Ian
Abstract : This synthesis concludes this Special Issue (II) by revisiting and extending the synthesis which concluded Special Issue (I) in December 2015. The focus is again on instrument-action alignments in governance in terms of their nature, pervasiveness and warranting. Of particular interest are inherent challenges of diversity, interconnection and responsibility which require appreciative, integrative and legitimation capacities. These challenges and capacities, involving their form, significance and intertwining, are central to the thematic interests and concerns of the Special Issues.